(untitled) (قضايا سياسية, 2025)
The study focuses on future scenarios for Iraqi foreign policy, between alignment and neutrality. The results highlight that alignment with an external axis may provide short-term support, but it restricts the independence of national decision-making and exacerbates challenges. Positive neutrality, on the other hand, provides an opportunity to enhance Iraq's sovereignty, diversify its partnerships, and enhance its regional role as a mediator. Negative neutrality, on the other hand, leads to a decline in Iraq's regional and international role and increases the fragility of national politics. The study concludes that adopting a policy of positive neutrality is the most appropriate option for achieving a balance between protecting sovereignty and enhancing Iraq's regional and international standing.